A Preliminary Scoping Review Study of the Progress of Social Media Adoption as an Educational Tool by Academics in Higher Education - Brady, Mairead; Perez, Eva (My University, 2018)
This paper presents a preliminary scoping review exploring the evidence landscape regarding academic staff experiences and perceptions of social media adoption as an educational tool in higher education. The goal of this paper is to examine 10 empirical studies of social media adoption in teaching and learning by academics in preparation for a proposal for a systematic literature review. Consequently, this scoping study assisted in the development of a review protocol which established the inclusion and exclusion criteria for conducting this systematic review at a future date. This paper will present the first stage of carrying out a systematic review: planning the review and presenting the results of the scoping study. The findings of this scoping study revealed that academics are slow in adopting social media within teaching and academics that have adopted the use of social media do so primarily for sharing relevant information and resources easily with students rather than for teaching purposes. Overall, the adoption of social media as an educational tool is faced with many challenges, such as cultural resistance, pedagogical issues, lack of institutional support and time investment. The results also indicate that teaching styles, demographic factors, privacy issues and previous experience can influence academic staff’s decision to adopt social media for teaching purposes.
PUBLISHED
Keywords: Social media; Teaching and learning; Higher education; Digital Engagement; Technology adoption in Education; Education